Das Praxisbeispiel in der Homiletik - Greifenstein, Johannes (Pastoraltheologie, 2017)
The article distinguishes two types, a "resultative treatment" which describes what a sermon developed in accordance with a homiletic theory looks like, and a "procedural treatment" where the theory is developed from actual instances of preaching. For both types a number of cases spanning the 19th century to the present are presented.Homiletic theory should more consciously make clear why it uses examples and in which way.